On the uniqueness of solutions of the Dirichlet and Neumann problems for an elliptic second-order differential equation on a semiaxis - Gorbachuk, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
For an elliptic second-order differential equation in a Banach space, we give a description of all solutions of the homogeneous Dirichlet and Neumann problems and establish conditions under which these problems are uniquely solvable.